Quando il fronte diventa ponte. Esperienze di confine. (Altre Modernità, 2018)
As far as I can see, there is a real place that actualise, better than any other one, the double nature meant by the term 'border' - a sort of oxymoron, in terms of etymology: the trench.Similarly, it does exist an author who experienced, comprehended and cried that duplicity out: Giuseppe Ungaretti. Forced to live a dramatic experience within the boundary line, he succeeded in crossing the historical, political, ideological and existential boundary between himself and 'the other'. Furthermore, he did it without any constriction, as it was a 'natural' and unavoidable 'step', as a result of his human nature. Crossing the boundary inevitably meant the reformulation of the relationship with 'the other', where 'the other' means person, landscape and 'absolute'; likewise, this led the author to a deep reconsideration of the current linguistic and literary conventions. The traditional poetical language had proved to be completely inadequate in front of the dramatic condition of the modern man. In order to demonstrate the relevant role of the border in this evolution, it will be made a comparison between Ungaretti's experience and the one of other two Italian intellectuals. Those, despite of living similar – even though not identical – war experiences, didn't come to the same conclusion as our poet, neither ideological nor literary.Beyond the natural differences in their personality and artistic sensitivity, as far as Giani Stuparich is concerned, it is another real border to make the difference: the boundary line between Italy and Austro-Hungarian Empire. Despite belonging to 'there', he felt himself 'here'. On the contrary, talking about Carlo Emilio Gadda, what appears relevant is the role he played in the Army during the war: he was an officer and he didn't live in the trenches. That seems to have influenced his conception of the war and to have prevented him from 'crossing the boundary'.
Keywords: confine; trincea; Altro; Ungaretti; Stuparich; Gadda